Heavy metal tolerance genes alter cellular thermodynamics in Pseudomonas putida and river Pseudomonas spp. and influence amebal predation. Issue 2 (14th August 2013) - McTee, Michael R.; Gibbons, Sean M.; Feris, Kevin; Gordon, Nathan S.; Gannon, James E.; Ramsey, Philip W.
Abstract Predation rates were measured for two Acanthamoeba castellanii strains feeding on metal‐tolerant and metal‐sensitive strains of Pseudomonas putida and compared with cellular thermodynamic data. Predation rates by A. castellanii strain ATCC 30010 correlated with cell volume of the prey. To explore whether this observation could be environmentally relevant, pseudomonad species were isolated from a pristine and a metal‐contaminated river and were paired based on phylogenetic and physiological relatedness. Then, cellular thermodynamics and predation rates were measured on the most similar pseudomonad pair. Under cadmium stress, the strain from contaminated river sediments, Pseudomonas sp. CF150, exited metabolic dormancy faster than its pair from pristine sediments, Pseudomonas sp. N9, but consumed available resources less efficiently (more energy was lost as heat). Predation rates by both strains of ameba were greater on Pseudomonas sp. CF150 than on Pseudomonas sp. N9 at the highest cadmium concentration.